(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Health valued juices extracted from various available fruits are familiar to people all over the world. Mango is an important fruit because of its abundance, taste and health value. Mango juice is made from mango extract. So, investigation of mango juice is needed for evaluation its health value by determining different types of nutritive parameter and comparative studies. Our research deals with the investigation of 8 types of mango juices of different local and foreign companies available in the markets of Bangladesh for the determination of pH, moisture content, TSS, sugar content, fat, ascorbic acid, protein, acidity and ash content. All the parameters are determined by the conventional physical and chemical methods including Floch method, Kjeldal method. This study demonstrates that mango juices contain a considerable amount of different types of these nutritive factors. The results of this study were compared to the original mango extract which will be helpful for consumers to consider the nutritional and safety of mango juices. J. Environ. Sci. & Natural Resources, 8(1): 95-98 2015